Efficacy and effects of palifermin for the treatment of oral mucositis in patients affected by acute lymphoblastic leukemia. Issue 4 (2nd April 2016) - Lucchese, Alessandra; Matarese, Giovanni; Ghislanzoni, Luis Huanca; Gastaldi, Giorgio; Manuelli, Maurizio; Gherlone, Enrico
Abstract: This randomized-controlled trial studied the efficacy of palifermin, administered as a dose during hematopoietic stem cell transplant (HSCT) therapy, as primary prophylaxis on pediatric patients with acute lymphoblastic leukemia in order to reduce oral mucositis (OM). Patients in the palifermin group were randomly assigned to receive palifermin, 60 μg/kg, intravenously as a single dose 3 days before and 0, +1, and +2 post autologous HSCT infusion. The patients in the control group received only a placebo treatment. OM-related assessments were the WHO oral-toxicity scale and the patient-reported outcomes. There was a statistically significant reduction in the incidence of OM grade 3 and 4 in the palifermin group compared to the control group. There was also a reduction in the degree of severity of OM in the palifermin group (1.65 grade respect to 2.33 in the control group). Palifermin could prevent the recurrence of severe OM and improve the quality of life in patients with acute lymphoblastic leukemia (ALL).